Bio-lubricating base oil from castor oil (Ricinous communus) - Banik, SK; Rabeya, T; Hasan, M; Saha, D; Islam, MS (Bangladesh Journal of Scientific and Industrial Research, 2022)
Production and characterization of bio lubricating base oil from non-edible castor seed oil has been studied. Castor oil was extracted from castor seed by solvent extraction method. KOH catalyzed transesterification process was used to produce bio-lubricating oil. Ethanol was used as alcohol in the transesterification process. Optimum condition for bio-lubricating base oil production was 40% ethanol, 0.45% KOH at 75oC for reaction time of 90 min. and the yield was 98%. Important properties of produced bio-lubricating oil like acid value (0.58 mg KOH/g), flash point (235oC), density (0.890 g/cc), pour point (-15oC) and viscosity (131.90 and 16.5 cSt at 40 and 100 oC respectively) etc. were analyzed. The properties were found to be analogues to conventional commercial lubricating oil. This renewable base oil from castor seed could be an attractive and environment friendly alternative to base oil from petroleum sources. Bangladesh J. Sci. Ind. Res. 57(1), 7-14, 2022